Digital marketing excellence : planning, optimizing and integrating online marketing - Chaffey, Dave (Routledge, 2018)
Now in its fifth edition, the hugely popular Digital Marketing Excellence: Planning, Optimizing and Integrating Online Marketing is fully updated, keeping you in line with the changes in this dynamic and exciting field and helping you create effective and up-to-date customer-centric digital marketing plans.